(untitled) (World Bulletin of Social Sciences, 2022)
In this article, the ideas of the encyclopedist Abu Rayhan Beruni on the issues of building a person, state and virtuous society, which are important not only for his time, but also for the present time, are put forward. The thinker recognizes the role of material needs of people in the creation of society. Needs, that is, the necessary demand for food, clothing, etc., material factors encourage people to live together. "The needs are diverse and countless. Only a number of people can provide them together. He states that people need to establish cities for this. It urges the heads of state and all citizens to do well, to live on the basis of mutual help, such a call has great educational and philosophical value for modern societies.